Urban Porosity: Integration Between City And Nature - Silva, Genivaldo Borges da (Latin American Journal of the Built Environment & Sustainability, 2025)
Objective – To demonstrate how the integration between city and nature can be promoted in the Complexo Córrego da Mula–Lagoa Bonita in Campinorte (GO), through nature-based solutions (NbS) aimed at the rehabilitation of degraded environments.Methodology – Qualitative and exploratory research, grounded in the principles of urban ecology (Hough, 1996; Spirn, 2003) and the concept of green and blue infrastructure (Pellegrino, 2011; Benedict; McMahon, 2006). It combined bibliographic review, spatial analysis, and participatory practices inspired by tactical urbanism (Lydon; Garcia, 2015; Sansão Fontes, 2018) and critical environmental education (Freire, 1987; Guimarães, 2000; Loureiro, 2012). Activities included pedagogical workshops, community records, and ephemeral actions with students and teachers of Dalva Marques Costa Municipal School.Originality/Relevance – Addresses the gap regarding urban rivers in small Cerrado towns by operationalizing NbS/green-blue infrastructure at the micro-basin scale, based on spatial analysis and school–university–community practices. It introduces indicators linking pedagogical actions to water rehabilitation and offers replicable and cost-effective guidelines for local policies.Results – Problems such as riparian degradation, absence of vegetation, lack of basic sanitation, excessive impermeabilization, risk of soil, water, and air contamination, and high temperatures due to heat islands were identified. Potentialities were also observed, including native vegetation, wetlands, and water availability. These environments support the integration between people and ecosystems, since in addition to contributing to urban aesthetics, such green and aquatic areas can also serve as spaces for gatherings, permanence, leisure, recreation, and health.Theoretical/Methodological Contributions – Consolidates the articulation of urban ecology, green and blue infrastructure, critical environmental education, and tactical urbanism-inspired actions, offering a methodological framework replicable in small towns.Social and Environmental Contributions – Strengthens community bonds, broadens local environmental awareness, and suggests guidelines for public policies on water and urban rehabilitation in the Cerrado.
Keywords: water resilience; urban ecology; green and blue infrastructure